Pengaruh Perlakuan pH dan Suhu terhadap Stabilitas Ekstrak Alga Merah (Gracilaria sp.) sebagai Pewarna Alami - Keron, Odilia; Wrasiati, Luh Putu; Gunam, Ida Bagus Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
Phycoerytrin is a red pigment found in red algae. Red algae Gracilaria sp. potential to be a source of natural dye because it contains phycoerythrin. Phycoerythrin is unstable to light, pH, and temperature. The purpose of this study was to determine the effect of pH and temperature on the stability of the dye extract from the red algae Gracilaria sp. and determine the pH and temperature that best maintain the constancy of the red algae Gracilaria sp. extract during storage. The design in this study used a completely randomized design with two factors, namely pH and temperature. First factor was the pH treatment which consist of three levels namely pH 4, pH 7 and pH 10 and second factor was initial temperature consist of two levels, namely 4±2?C and 28±2?C. The results showed that pH had a very significant effect (P<0.01) on the total phycoerythrin, brightness (L*), redness (a*) and yellowness (b*) at weeks 2, 3, 4. Temperature treatment has a very significant effect on the total phycoerythrin and brightness (L*) at weeks 3 and 4, as well the level redness (a*) and the level yellowness (b*) at weeks 2, 3 and 4. At pH 4 and cold temperature (4±2?C) were the best treatments to maintain the stability of the red algae Gracilaria sp. extract during storage. They had the lowest decrease in phycoerythrin levels and redness (a*), and had the smallest increase in brightness (L*) and yellowness (b*). Extract that were stored for 4 weeks with pH 4 and temperature 4±2?C treatment had decrease in total phycoerythrin, increase in brightness (L*), decrease in redness (a*), and increase in yellowness (b*) successively was 13.04%, 0.47%, 6.58%, dan 3.50%.            Keywords : Gracilaria sp. extract, phycoeriythrin, pH, temperature, stability